Clinical efficacy and safety of abatacept in methotrexate-naive patients with early rheumatoid arthritis and poor prognostic factors. Issue 12 (5th January 2009) - Westhovens, R; Robles, M; Ximenes, A C; Nayiager, S; Wollenhaupt, J; Durez, P; Gomez-Reino, J; Grassi, W; Haraoui, B; Shergy, W; Park, S-H; Genant, H; et al.
Abstract : Objectives: To assess the efficacy and safety of abatacept in methotrexate-naive patients with early rheumatoid arthritis (RA) and poor prognostic factors. Methods: In this double-blind, phase IIIb study, patients with RA for 2 years or less were randomly assigned 1 : 1 to receive abatacept (∼10 mg/kg) plus methotrexate, or placebo plus methotrexate. Patients were methotrexate-naive and seropositive for rheumatoid factor (RF), anti-cyclic citrullinated protein (CCP) type 2 or both and had radiographic evidence of joint erosions. The co-primary endpoints were the proportion of patients achieving disease activity score in 28 joints (DAS28)-defined remission (C-reactive protein) and joint damage progression (Genant-modified Sharp total score; TS) at year 1. Safety was monitored throughout. Results: At baseline, patients had a mean DAS28 of 6.3, a mean TS of 7.1 and mean disease duration of 6.5 months; 96.5% and 89.0% of patients were RF or anti-CCP2 seropositive, respectively. At year 1, a significantly greater proportion of abatacept plus methotrexate-treated patients achieved remission (41.4% vs 23.3%; p<0.001) and there was significantly less radiographic progression (mean change in TS 0.63 vs 1.06; p = 0.040) versus methotrexate alone. Over 1 year, the frequency of adverse events (84.8% vs 83.4%), serious adverse events (7.8% vs 7.9%), serious infections (2.0% vs 2.0%), autoimmune disorders (2.3% vs 2.0%) and malignancies (0.4% vs 0%) was comparable for abatacept plus methotrexate versus methotrexate alone. Conclusions: In a methotrexate-naive population with early RA and poor prognostic factors, the combination of abatacept and methotrexate provided significantly better clinical and radiographic efficacy compared with methotrexate alone and had a comparable, favourable safety profile.